Epstein-Barr virus-negative diffuse large B-cell post-transplant lymphoma in an Epstein-Barr virus-positive recipient - Lee, C; Vincentelli, H; Visuri, J; Knight, S; Ploeg, R (Cureus, 2021)
Post-transplant lymphoproliferative disease (PTLD) can arise as a complication after solid organ transplantation. Epstein-Barr virus (EBV) infection is a known risk factor and is known to drive disease manifestation. PTLD can occur in EBV-negative recipients and with EBV-negative donor organs, however, EBV-negative PTLD pathogenesis is unknown. Here, we present PTLD presenting as intussusception in a patient with a historic simultaneous pancreas-kidney transplant (SPK). This case study presents the first documented case of EBV-negative post-transplant lymphoproliferative disease in an EBV-seropositive SPK recipient from an EBV-positive donor. Here we describe the diagnosis and management of this patient, discuss the differences between EBV positive and negative driven post-transplant lymphoproliferative disease, and highlight areas of research opportunity in the latter.